Biomass and Carbon Stock Dynamics in Tropical Evergreen and Deciduous Forests of Uttara Kannada District, Western Ghats, India (Global Journal of Science Frontier Research, 2016)
Western Ghats is one of the biodiversity 'hotspots' of the world and currently, there is limited evidence on the status and dynamics of tropical forests in the context of human disturbance and climate change. This study presents the findings of the study conducted under a citizen science programme. The biomass and carbon stocks in the evergreen and deciduous forests of the study area are comparable to the standing biomass of other tropical forests and range from 344-417 tC. There are no major differences between carbon stocks in less and more disturbed forests, which is of significance, given the large dependence of communities on the more disturbed forests. Periodic and long-term monitoring of forests is necessary in the context of potential increased human pressure and climate change to plan and manage forests for mitigation as well as adaptation in a synergistic manner.
Keywords: carbon stock dynamics; evergreen; deciduous; tropical forests; uttara kannada; western ghats; human disturbance